The Persistence of Shalawat Ngelik in Kampung Mlangi, Yogyakarta: Habitus, Capital, and Regeneration - Dewi, Arviana; Alimi, Moh. Yasir (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
This study examines the persistence of Shalawat Ngelik, a traditional form of religious musical performance practiced in Kampung Mlangi, Yogyakarta. Although earlier studies have documented the historical background and cultural characteristics of this tradition, the social mechanisms that enable its continuity across generations remain insufficiently explored. This research analyzes Shalawat Ngelik as a social practice using Pierre Bourdieu’s conceptual framework of habitus, capital, and field. The study employs a qualitative case study design. Data were collected through in-depth interviews with community members and performers, field observations during religious gatherings and practice sessions, and supporting documentation related to the activities of the Shalawat Ngelik group. The findings show that the persistence of Shalawat Ngelik is sustained through the interaction of several forms of capital embedded in the religious life of the community. Social capital emerges through networks associated with Nahdlatul Ulama (NU) and communal religious activities. Cultural capital appears in the musical competence required to perform the repertoire and distinctive vocal techniques of Shalawat Ngelik. These competencies gradually develop into symbolic capital as skilled performers gain recognition within community events. Economic capital operates collectively through practices such as berkat, which support communal performances without turning the tradition into a commercial activity. The study also finds that the regeneration of Shalawat Ngelik occurs through the reproduction of religious and cultural habitus rooted in everyday participation rather than through formal institutional training. This study shows that the continuity of Shalawat Ngelik is maintained through the interaction of social networks, cultural competence, symbolic recognition, and communal support embedded in local religious life. The findings contribute to discussions on the persistence of local religious traditions and the role of social practice in sustaining cultural expressions within contemporary Muslim communities.